2016
DOI: 10.1038/srep23795
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-laden cells differentially distributed in the aging brain are functionally active and correspond to distinct phenotypes

Abstract: We characterized cerebral Oil Red O-positive lipid-laden cells (LLC) of aging mice evaluating their distribution, morphology, density, functional activities and inflammatory phenotype. We identified LLC in meningeal, cortical and neurogenic brain regions. The density of cerebral LLC increased with age. LLC presenting small lipid droplets were visualized adjacent to blood vessels or deeper in the brain cortical and striatal parenchyma of aging mice. LLC with larger droplets were asymmetrically distributed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 61 publications
2
80
0
Order By: Relevance
“…Indeed, HNE can impair lysosome function in cerebral cortical neurons, resulting in the accumulation of undegraded cargos and subsequent cell death (Zhang et al, 2017). Lipids also accumulate in autophagic vesicles (lipofuscin) or lipid-laden vesicles (Sulzer et al, 2008; Shimabukuro et al, 2016) in neurons during aging. Proteasome dysfunction and overload also occur during brain aging, which manifests as accumulations of polyubiquitinated proteins in neurons (Graham and Liu, 2017).…”
Section: Cellular and Molecular Hallmarks Of Brain Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, HNE can impair lysosome function in cerebral cortical neurons, resulting in the accumulation of undegraded cargos and subsequent cell death (Zhang et al, 2017). Lipids also accumulate in autophagic vesicles (lipofuscin) or lipid-laden vesicles (Sulzer et al, 2008; Shimabukuro et al, 2016) in neurons during aging. Proteasome dysfunction and overload also occur during brain aging, which manifests as accumulations of polyubiquitinated proteins in neurons (Graham and Liu, 2017).…”
Section: Cellular and Molecular Hallmarks Of Brain Agingmentioning
confidence: 99%
“…Within the brain, the metabolism of multiple lipid species is altered during aging as indicated by the accumulation of long-chain ceramides (Cutler et al, 2004) and lipid-laden cells (Shimabukuro et al, 2016), and a decline in brain tissue levels of omega-3 fatty acids (Denis et al, 2013). Genetic evidence also links lipid metabolism to poor brain outcomes during aging.…”
Section: Cellular and Molecular Hallmarks Of Brain Agingmentioning
confidence: 99%
“…This indicates that similar to mammals, there are few LDs in C. elegans neurons under normal conditions. It has been reported that both aging and general obesity may increase LD accumulation in non-adipose tissues (Palikaras, Mari et al, 2017, Shimabukuro, Langhi et al, 2016, Zhou, Grayburn et al, 2000.…”
Section: Lds Accumulate In Neurons Of Both Atgl-1 and Lid-1 Mutantsmentioning
confidence: 99%
“…That they may have important functions in disease has recently been suggested in a drosophila model where lipid droplet formation has been reported in glia at the onset of neurodegeneration 30,31 . Oil-red-O positive "lipid-laden" cells, including neurons, astrocytes, ependymal cells and Iba1 + cells have recently been reported in mice and shown to increase with age 32 . Lipid droplets were also induced in LPS-treated mouse hippocampal slice cultures and in the N9 microglia cell line [33][34][35] .…”
Section: Introductionmentioning
confidence: 99%